2020
DOI: 10.1186/s40168-019-0774-7
|View full text |Cite
|
Sign up to set email alerts
|

Mobile resistome of human gut and pathogen drives anthropogenic bloom of antibiotic resistance

Abstract: Background: The impact of human activities on the environmental resistome has been documented in many studies, but there remains the controversial question of whether the increased antibiotic resistance observed in anthropogenically impacted environments is just a result of contamination by resistant fecal microbes or is mediated by indigenous environmental organisms. Here, to determine exactly how anthropogenic influences shape the environmental resistome, we resolved the microbiome, resistome, and mobilome o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(69 citation statements)
references
References 49 publications
0
66
0
3
Order By: Relevance
“…Freshwater environments, including rivers, are considered reservoirs and dissemination routes for AMR 34 . Several studies have clearly depicted a larger increase in ARGs in human-impacted river sites than in the pristine river sites, indicating the effects of anthropogenic activities on the river resistome 35 37 . The river resistome is important for the potential reintroduction of AMR in humans because rivers are a major source of drinking water and irrigation water for agriculture 38 , 39 .…”
Section: Antibiotic Resistome In One-health Sectorsmentioning
confidence: 99%
“…Freshwater environments, including rivers, are considered reservoirs and dissemination routes for AMR 34 . Several studies have clearly depicted a larger increase in ARGs in human-impacted river sites than in the pristine river sites, indicating the effects of anthropogenic activities on the river resistome 35 37 . The river resistome is important for the potential reintroduction of AMR in humans because rivers are a major source of drinking water and irrigation water for agriculture 38 , 39 .…”
Section: Antibiotic Resistome In One-health Sectorsmentioning
confidence: 99%
“…As anthropogenic activities largely shape the resistome of different environments, transmission of resistant genes between bacteria in a community can be influenced by its contamination with human and animal feces and its impact is largely driven not by the presence of resistant bacteria but rather from the presence of human-related mobile resistance genes [44]. If poor sanitation, manifested by fecal contamination, of a given community is the key to transmit and maintain resistant clones, the reduction of antibiotic consumption will not be sufficient to control antimicrobial resistance.…”
Section: Hygiene/fecal Colonizationmentioning
confidence: 99%
“…Plasmids are mobile genetic elements found in high abundance in the bacterial populations of bovine rumen [36], which play a major role in the spread of antimicrobial resistance through horizontal gene transfer [37]. Metagenomic approaches have been used to characterize plasmid encoded ARGs in several non-biological habitats such as activated sludge [38,39] as well as the human gut [40]. We found that aadA and tetW were the most abundant plasmid-associated ARG in the rumen of beef steers.…”
Section: Discussionmentioning
confidence: 94%